GOVERNMENT LEGAL RESPONSIBILITY FOR PAYMENT OF COMPENSATION COSTS FOR THE BUNTU KUNIK BERKENDEK TANA TORAJA AIRPORT CONSTRUCTION PROJECT - Andrito Palipadang; Marwati Riza; Muhammad Ilham Arisaputra (Universitas Labuhanbatu, 2023)
The application of the precautionary principle at the stage of land acquisition for the construction of the airport, but not yet fully implementing the precautionary principle and implementation that is not transparent because it does not involve the full participation of the community, especially the people affected by the development and the inventory/identification of documents that were not carried out properly by the Land Acquisition Committee which resulted in an error in paying compensation.Â Keywords: Precautionary Principle, Legal Consequences, Compensation